Biological Evaluation of Platinum(II) Sulfonamido Complexes: Synthesis, Characterization, Cytotoxicity, and Biological Imaging. (13th September 2022) - Maladeniya, Charini; Darshani, Taniya; Samarakoon, Sameera R.; Fronczek, Frank R.; Sameera, W. M. C.; Perera, Inoka C.; Perera, Theshini
Abstract : Platinum-based compounds are actively used in clinical trials as anticancer agents. In this study, two novel platinum complexes, ( C 1 = [PtCl2 ( N (SO2 quin)dpa)], C 2 = [PtCl2 ( N (SO2 azobenz)dpa)]) containing quinoline and azobenzene appended dipicolylamine sulfonamide ligands were synthesized in good yield. The singlet attributable to methylene CH2 protons of the ligands of C1 and C2 appears as two doublets in 1 H NMR spectra, which confirms the presence of magnetically nonequivalent protons upon coordination to platinum. Structural data of N (SO2 quin)dpa (L1), N (SO2 azobenz)dpa (L2) and PtCl2 ( N (SO2 quin)dpa) confirmed the formation of the desired compounds. Time-dependent density functional theory calculations suggested that the excitation of L1 show quin-unit-based π⟶π ∗ excitations (i.e., ligand-centered charge transfer, LC), while C1 shows the metal-ligand-to-ligand charge-transfer (MLLCT) character. L1 displays intense fluorescence from the 1 LC excited state, while C1 gives phosphorescence from the 3 LC state. Mammalian cell toxicity of ligands and complexes was assessed with NCI–H292 nonsmall-cell lung cancer cells. Further, C1 and C2 showed significantly low IC50 values compared with N (SO2 azobenz)dpa and PtCl2 ( N (SO2 quin)dpa). Fluorescence imaging data of both ligands and complexes revealed the potential fluorescence activity of these compounds for biological imaging. All four compounds are promising novel candidates that can be further investigated on their usage as potential anticancer agents and cancer cell imaging agents.